![x \: cube + 2x \: cube - x - 2 x \: cube + 2x \: cube - x - 2](https://tex.z-dn.net/?f=x+%5C%3A+cube+%2B+2x+%5C%3A+cube+-+x+-+2)
Factorise
siddhartharao77:
it cant be factorized!
Answers
Answered by
3
Hope u like my process
=====================
Here you have a simple mistake on the question of writing cube in place of square.
Thus I am correcting the question and providing u with the answer.
_______________________
The required factorization for
=> x³ +2x² - x - 2. is
= > x³ + 2x² - x - 2
= x³ + x² +x² +x - 2x - 2
= x²(x +1) +x(x +1) - 2(x+1)
= (x +1)(x² +x - 2)
= (x +1)(x² + 2x - x - 2)
= (x +1)[ x(x+2) - 1(x+2)]
= (x +1)(x-1)(x+2)
___________________
Alternative way
=-=-=-=-=-=-=-=-=-=
=> x³ +2x² - x - 2
= x²(x +2) - 1(x +2)
= (x² - 1)(x +2)
= (x - 1)(x +1)(x+2)
_[since, (x² - 1) = (x-1)(x+1)]__
So the required factorization is
![= > \boxed{ \underline{ \bold{( \green{x - 1})( \green{x + 1})( \green{x + 2})}}} = > \boxed{ \underline{ \bold{( \green{x - 1})( \green{x + 1})( \green{x + 2})}}}](https://tex.z-dn.net/?f=+%3D+%26gt%3B+%5Cboxed%7B+%5Cunderline%7B+%5Cbold%7B%28+%5Cgreen%7Bx+-+1%7D%29%28+%5Cgreen%7Bx+%2B+1%7D%29%28+%5Cgreen%7Bx+%2B+2%7D%29%7D%7D%7D)
____________________________
=-=-=-=-=-=-=-=-=-=-=-=-=-=-=-=-=
Hope this is ur required answer
Proud to Help you.
=====================
Here you have a simple mistake on the question of writing cube in place of square.
Thus I am correcting the question and providing u with the answer.
_______________________
The required factorization for
=> x³ +2x² - x - 2. is
= > x³ + 2x² - x - 2
= x³ + x² +x² +x - 2x - 2
= x²(x +1) +x(x +1) - 2(x+1)
= (x +1)(x² +x - 2)
= (x +1)(x² + 2x - x - 2)
= (x +1)[ x(x+2) - 1(x+2)]
= (x +1)(x-1)(x+2)
___________________
Alternative way
=-=-=-=-=-=-=-=-=-=
=> x³ +2x² - x - 2
= x²(x +2) - 1(x +2)
= (x² - 1)(x +2)
= (x - 1)(x +1)(x+2)
_[since, (x² - 1) = (x-1)(x+1)]__
So the required factorization is
____________________________
=-=-=-=-=-=-=-=-=-=-=-=-=-=-=-=-=
Hope this is ur required answer
Proud to Help you.
Similar questions